Exceptions Set Out a Principle Binding Force Contract - Touati, Basma; Atmani, Billal (Journal of Legal Studies and Researches, 2022)
In some cases specific exclusively in civil law, judge and legislator may deviate from the principle of indivisibility of changing contract as required by the binding force of the contract, to mitigate the consequences resulting by an absolute application of freedom contractual, on the one hand, and for the objective of achieving contractual justice on the other hand.